THE EFFECT OF SERVICE QUALITY AND RELATIONAL EFFORTS ON TRANSACTION SATISFACTION, RELATIONAL OUTCOME AND CUSTOMER RETENTION IN RETAIL BUSINESS IN THE CITY OF BANJARMASIN - noor ritawaty, (Archives of Business Research, 2019)
ABSTRACT The study aims to analyze the influence of the services quality and relational efforts relational satisfaction, relational outcomes and retention of customers in the retail business in the city of Banjarmasin. The population in this study is the consumer supermarket in the city of Banjarmasin, such as Hypermart, Giant. Lottemart, and Ramayana Robinson. Given the respondents in this study is homogeneous, so that the sample collection technique is systematic random sampling with selected respondents must meet predetermined criteria standards. because the population is not limited to, the proportional method used to determine the number of samples as many as 200. Data analysis using SPSS and AMOS 20.0 software. From the test results that, only 7 hypothesis have a significant effect, namely: services Quality has significantly influence to customer satisfaction of retail transactions in Banjarmasin. Quality of service is a significant effect on the retention of retail customers in the city of Banjarmasin. Relational Efforts significant effect on satisfaction of customer transactions in Banjarmasin. Relational efforts has significant influence to outcome relational. Satisfaction transaction has significant influence to outcome relational retail customers in the city of Banjarmasin. Transactions Satisfaction has significant effect to the customer retention of retail customers in the city of Banjarmasin. Outcome relational has significant effect on the customersretention in the city of Banjarmasin.While two other hypothesis has not significant are: Quality of service not significant effect on relational outcomes retail customers in the city of Banjarmasin. Efforts relational no significant effect on the retention of retail customers in the city of Banjarmasin. Keywords: Service Quality, Relational Effort, Transaction Satisfaction, Relational Outcomes, Customer Retention